Numerical investigations of phase change material (PCM) based thermal control module (TCM) under the influence of low gravity environment. (March 2021) - Kansara, Keyur; Singh, V.K.; Patel, Rajesh; Bhavsar, R.R.; Vora, A.P.
Highlights: Effect of gravity (g) on melting and solidification of PCMs in 3D space is studied. PCM based Thermal Control Module (TCM) having fins is considered for the study. Three PCMs (Hexadecane, Acetic acid and Glycerol) are chosen for the present work. 'g' has significant influence on melting while less impact on solidification. Study will be useful for designing TCMs for low gravity environment. Abstract: The present work aims to address the effect of gravity on the melting and solidification of phase change materials (PCM) in an optimized thermal control module (TCM) having pin fins as heat transfer enhancers. The enthalpy-porosity technique is used to model the solid-liquid phase change process and flow evaluation inside TCM. The melting and solidification processes are simulated for three-phase change materials (hexadecane, acetic acid, and glycerol) at different values of gravitational accelerations (i.e., melting at g, g/2, g/10, g/20, g/40, g/80 and solidification at g, g/80). The governing equations are non-dimensionalized, and results are reported in the form of dimensionless numbers. It is evident from the study that the gravity environment significantly influences the melting and solidification of PCM. The research shows that the value of PCM average liquid fraction gradually decreases by 18% as the value of gravitational acceleration reduces from g to g/80. The effect of the natural convection is noticeable on the melting of hexadecane and acetic acid. However, the minimal effect of natural convection was observed on the melting of glycerol due to highly viscous nature and faster heat propagation through the material. The effect of gravity on the solidification is small compared to the melting because the conduction heat transfer primarily dominates the solidification process. The present study provides information on the effect of gravity on performance parameters of the PCMs, which helps determine the size of the heat sinks operating under terrestrial and space environments.